Knowledge, Attitude and Practice towards Cardiovascular Disease Risk Factors and Preventive Measures among Preclinical Medical Students in UniKL RCMP - Padmavathy K.M; Fadhil Imran Bin Yuhaznel; Kriishor U; Krishant U; Nor Fatin Amylia Binti Abdul Salam; Saravaana kumaar M; Wanna Thaqeefah Binti Muhamad Herman; Rohith Sharan S (Asian Journal of Medicine & Health Sciences, 2022)
Background: Cardiovascular Disease (CVD) is one of the leading causes of morbidity and mortality in Malaysia. The awareness about the disease and the factors affecting cardiovascular health among the younger generation is decisive in reducing the prevalence of CVD. The aim of the study was to explore and to compare the differences of the knowledge, attitude and practice (KAP) towards cardiovascular disease risk factors and preventive measures among preclinical medical students in Universiti Kuala Lumpur-Royal College of Medicine Perak (UniKL-RCMP). Methods: A cross-sectional survey was conducted among pre-clinical MBBS students of Year 1 and 2. The participants were randomly selected to participate in this study and were required to answer the survey questionnaire regarding the risk factors and preventive measures of CVD on Google™ Forms platform. The questionnaire was adapted from previously published papers that explored the parameters of interest. The responses were recorded as ‘Yes’, ‘No’, and ‘I don’t know’ for knowledge parameters, while the attitude and practice parameters followed a 5-point Likert scale. The data entry, cleaning, and analysis was done in the SPSS. Questions that had reverse scoring were appropriately adjusted during analysis. Results: In total 168 preclinical students (84 students from Year 1 and 84 students from Year 2) participated in this study. The composite mean scores of the knowledge, attitude, and practice parameters were 8.23 ± 2.46, 47.38 ± 9.24, and 22.73 ± 6.53, respectively. There were no significant (p>0.05) differences in the KAP scores between Year 1 and Year 2 students. Conclusion: The study was successful in exploring the knowledge, attitude and practice towards cardiovascular disease risk factors and preventive measures among preclinical medical students. The findings could be used to compare the study parameters with students of higher courses in the undergraduate medical program or the longitudinal change of the parameters among the same group of students.